The Role of Fibrinolytic System in Health and Disease - Kwaan, Hau C. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This is a review of the topic of fibrinolysis contributed by authors who are specialized in the clinical and basic studies of this topic. These include: the endothelial receptor of tissue plasminogen activator, by Dr. Katherine Hajjar; regulation of S100 by pml-rar-alpha oncoprotein, by Dr. O'Connell; receptor of urokinase type plasminogen activator, by Dr. M. Ploug et al.; tissue plasminogen activator induction in purjinjen neuron, by Dr. Seeds; fibrinolysis from the blood to the brain, by Dr. Robert Metcalf; tissue plasminogen activator induces the opening of the blood-brain barrier, by Dr. M. Yepes; fibrinolysis shutdown in trauma: a historical review and clinical application, by Drs. Hunter Moore and Ernest Moore; fibrinolysis in immunity, by Drs. K. Kolev and Robert Medcalf; the role of plasminogen activator inhibitor 1, by Drs. M. Erin, A.E. Boe, and E.A. Klyachko; and finally, persistent fibrinolysis shutdown is associated with increased mortality in severely injured trauma patients, by J.P. Meizoso.